A comparative analysis of perceived and actual walking behaviour in varying land use and time. (2nd January 2019) - Pun-Cheng, L. S. C.; So, C. W. Y.
ABSTRACT: It is widely recognised that walking can bring about a host of health benefits. In order to encourage more walking, raising the walkability of pedestrian paths is one option. Studies in the past have taken on this subject but have only focused on a single variable only. By using a questionnaire to identify a pedestrian's perception of the key variables of walkability and a map survey to explore his/her actual choice of paths in two different districts (residential and commercial) in Hong Kong, this study establishes an integrated picture covering several key variables affecting walkability. A qualitative analysis shows that most generally and individually perceived as preferred safe and comfortable walking environmental variables may not be reflected in actual walking behaviour, especially in a busy working district. As such, if walking is to be promoted, the government may consider increasing the greenness and width of walkways while navigation tools, which currently focus mainly on distance and time, can further be improved to include more behavioural variables.